C-reactive protein is associated with ventricular repolarization dispersion among patients with metabolic syndrome - Jani, Ylber; Rexhepi, Atila; Pocesta, Bekim; Kamberi, Ahmet; Ferati, Fatmir; Xhunga, Sotiraq; Serani, Artur; Lala, Dali; Zeqiri, Agim; Mirto, Arben (Journal of Cardiology and Cardiovascular Medicine, 2019)
Background: An increasing body of evidence indicates that inflammatory activation profoundly impacts the electrophysiological properties of cardiomyocytes. A marker of systemic inflammation such as C-reactive protein(CRP), is associated with all parameters of the Mtabolic syndrome(MetS) and that may result in adverse cardiac events via multiple effects, ultimately resulting in a prolongation of Action Potential duration (APD), and thereby of the QTC (QT corrected) interval on ECG. Objective: We sought to investigate the influence of CRP levels on the prevalence of prolonged QT-dispersion and prolonged Tpeak-Tend –dispersion in the patients with MetS. Methods: We conducted a multicenter observational cross-sectional study. The study population consisted of 200 patients with MetS, stratified in two groups:103 participants (50 females and 53 males) with level of CRP>3mg/l, and 97 participants (47 females and 50 males) with level of CRP<3mg/l), who attended outpatient visits at general cardiology Health Care Clinics during 1 calendar year. For the analysis of the ECG, we performed a manual measurement of the values using a digital caliper with measuring range of 0-150 mm, 0.01 mm resolution, and 0-100 ± 0.02 mm accuracy. QT interval dispersion was obtained by the difference between the maximum and the minimum QT intervals found in the 12-lead electrocardiogram. The Tpeak-Tend interval was obtained from the difference between QT interval and QTpeak interval. Results: Prolonged QTC. dispersion, was found in 51.4% of participants with level of CRP>3mg/l and in 32.9% of with level of CRP<3mg/l, the differences were statistically significant. (p=0.004). The results showed that 51.4% participants with level of CRP>3mg/l had a prolonged Tpeak-Tend interval, and 32.9% of participants with level of CRP<3mg/l had prolonged Tpeak-Tend interval. Difference were statistically significant.( p=0.04). There were significant association of increased levels of CRP and QTC-dispersion (OR = 2.486, 95% CI 1.389-4.446).There were significant association of increased levels of CRP with Tpeak-Tend Dispersion (OR=2.239,95%CI 1.262-3.976). Prolonged QTC max. Interval OR=2.236,%CI 1.246-4.014),Prolonged Tp-Te-interval. (OR=2.367, 95%CI 1.327-4.222), also there were significant association of increased levels of CRP with BMI. (OR=1.154, 95%CI 1.095-1.227) and significant association of increased levels of CRP with presence of uncontrolled glicemia.(OR=1.779, 95%CI 1.014-3.12). Conclusion: We think we proved the hypothesis that patients with MetS and high level of CRP have higher prevalence of QT- dispersion and Tpeak-Tend dispersion than patients with MetS and lower level of CRP. These findings have both epidemiological and clinical relevance, also these findings might lend further insight into potential mechanisms by which MetS is associated with adverse cardiac events.